'Insulator bodies' are aggregates of proteins but not of insulators. - Golovnin, A.; Melnikova, L.; Volkov, I.; Kostuchenko, M.; Galkin, A.V.; Georgiev, P. (EMBO Reports, 2008)
Chromatin insulators are thought to restrict the action of enhancers and silencers. The best-known insulators in Drosophila require proteins such as Suppressor of Hairy wing (Su(Hw)) and Modifier of mdg4 (Mod(mdg4)) to be functional. The insulator-related proteins apparently colocalize as nuclear speckles in immunostained cells. It has been asserted that these speckles are 'insulator bodies' of many Su(Hw)-insulator DNA sites held together by associated proteins, including Mod(mdg4). As we show here using flies, larvae and S2 cells, a mutant Mod(mdg4) protein devoid of the Q-rich domain supports the function of Su(Hw)-dependent insulators and efficiently binds to correct insulator sites on the chromosome, but does not form or enter the Su(Hw)-marked nuclear speckles; conversely, the latter accumulate another (C-truncated) Mod(mdg4) mutant that cannot interact with Su(Hw) or with the genuine insulators. Hence, it is not the functional genomic insulators but rather aggregated proteins that make the so-called 'insulator bodies'.